Therapeutic benefits of gossypin as an emerging phytoconstituents of Hibiscus spp.: a critical review - Gayatri Jejurkar; Machindra Chavan (Future Journal of Pharmaceutical Sciences, 2023)
Abstract Background Flavonoids are one of the crucial secondary metabolites as several functions are carried out by flavonoids, including regulating cell growth, luring insects and pollinators, and defending against biotic and abiotic stressors. They are found in fruits, whole grains, vegetables, spices, tea, wine, herbs, and seeds. More than 4000 flavonoid compounds have been discovered and extracted through different techniques. Most flavonoids are frequently utilized in pharmaceuticals, nutraceuticals, cosmetics, and other products. A flavonol glucoside called gossypin is the primary phytochemical of herbs that comes under the "Malvaceae" family and can be found in many species, including Hibiscus esculentus, Gossypium indicum, and Hibiscus vitifolius, all have it in their flowers. Gossypin shows not only significant pharmacological activities but also a defence mechanism and protects against pathogens, UV radiation, etc. It has drawn much interest from researchers and scholars due to its benefits of few adverse effects, high efficacy, and simple preparation. Thus, the current review focuses primarily on the pharmacological accounts of gossypin in various acute and chronic diseases. The various assays and animal studies conducted in the past supported gossypin effects as supporting the concept of the objective of the title. The review also highlights various patents filled on gossypin’s importance and current market scenario. Conclusion Therefore, the technical contents based on pharmacological activities, patents and current market scenario provided in this paper for the improvement of research in numerous scientific fields will be helpful to researchers for suitable alternative designs of gossypin in various disorders. Graphical abstract